Reuse of Hydraulic Concrete Waste as a New Material in Construction Procedures: a Sustainable Alternative in Northwest Mexico - Gutiérrez Moreno, José Manuel; Mungaray Moctezuma, Alejandro; Hallack Alegría, Michelle (Revista de la Construcción. Journal of Construction, 2015)
Concrete demolition waste can be used as material for manufacturing high quality recycled coarse aggregates, which can replace natural aggregates to make hydraulic concrete mixes. In this study, the behavior of two hydraulic concrete mixes have been analyzed and tested under similar conditions. The comparison of natural concrete with 100% of natural aggregates, versus a specific recycled combination with 30% recycled coarse aggregate and 70% of natural coarse aggregate was studied. Results had shown a similar performance between the two concrete mixes after performing the mechanical tests in the laboratory. The incorporation of recycled aggregates in concrete allowed, in this case a competitive strength class one, which impact in reducing costs when applied in large concrete quantities. This alternative can represent a valuable environmental solution for construction and demolition waste disposal.